Me and my family tree - Sweeney, Joan, 1930-2017.; Trithart, Emma (New York : Dragonfly Books, 2018)
Using a family tree, a child explains how her brother, parents, grandparents, aunts, uncles, and cousins are related to her.
Kirkus Review
Kirkus Review, June 2018
1.5
K-3.
K-3
Keywords: Families -- Juvenile literature; Genealogy -- Juvenile literature; Families; Genealogy; Family; Genealogy; Picture books